INTENSIVE TEACHING METHODS IN RUSSIAN LANGUAGE CLASSES AT UNIVERSITIES AS A WAY TO INCREASE THE MOTIVATIONAL AND COGNITIVE SPHERE OF STUDENTS (Multidisciplinary Journal of Science and Technology, 2026)
This article is devoted to issues related to the use of interactive teaching methods in the study of the Russian language in universities. The article reveals the essence of interactive teaching methods and describes the methods, as well as the rules for their application, the role and importance of interactive learning in the personal and professional development of students is noted.